Ergonomic Risk Mitigation in Batik Stamping: A Hierarchical Task Analysis and REBA Study at Batik Komar Bandung - Yosua Novalesi; Yannes Martinus Pasaribu; Etika Vidyarini (Green Publisher Indonesia, 2025)
This research investigates postural risks faced by batik stamp workers at Batik Komar Bandung, employing Hierarchical Task Analysis (HTA) and Rapid Entire Body Assessment (REBA) to assess worker ergonomics. While batik holds immense cultural value, there is a lack of ergonomic research focusing on the well-being of workers in traditional batik production. The case study at Batik Komar Bandung involved 11 workers aged between 20 to 50 years, where work activities were documented through video and photographs, followed by HTA task analysis and REBA postural risk assessment. The findings reveal that the stamping stage, which constitutes 86.85% of the process, presents significant ergonomic risks, with a REBA score of 10 indicating high postural risk. Workers frequently use a ±1.1 kg stamp while maintaining bent postures for prolonged periods, contributing to potential musculoskeletal disorders. These findings underscore the urgent need for ergonomic interventions within the batik industry. The study proposes potential solutions, including workstation redesign, tool modification, and the implementation of regular rest periods to mitigate health risks. By addressing the ergonomic challenges in traditional batik production, this research highlights the importance of worker well-being and sustainability in the batik industry. Additionally, the study demonstrates the practical application of HTA and REBA in identifying postural risks and formulating effective interventions, contributing valuable insights to the growing field of ergonomic research in cultural industries.